2013
DOI: 10.1002/jctb.4108
|View full text |Cite
|
Sign up to set email alerts
|

Novel applications of dividing‐wall column technology to biofuel production processes

Abstract: Biofuels enjoy nowadays increased public and scientific attention, driven by key factors such as volatile oil price, the need for increased energy security, and concerns over greenhouse gas emissions from fossil fuels. However, in order to make biofuels a competitive alternative, the cost of production has to be significantly reduced by using enhanced process technologies. Distillation is heavily involved in the production processes of biofuels -taking the blame for the high energy requirements that have a neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 54 publications
0
51
0
Order By: Relevance
“…By process integration, the feed components can be distilled and separated with a small amount of utilities consumption [7,8]. The main advantage of a DWC is its possibility in saving both energy and capital costs [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The theoretical studies have shown that DWCs save at least 30 % of energy costs compared to the conventional schemes [7][8][9].…”
Section: Page 3 Of 29mentioning
confidence: 99%
“…By process integration, the feed components can be distilled and separated with a small amount of utilities consumption [7,8]. The main advantage of a DWC is its possibility in saving both energy and capital costs [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The theoretical studies have shown that DWCs save at least 30 % of energy costs compared to the conventional schemes [7][8][9].…”
Section: Page 3 Of 29mentioning
confidence: 99%
“…Purification of such processes by simple distillation is not possible. The reactive dividing‐wall distillation column (RDWC) was used for such reaction and separation systems . The production of biofuels and fuel additives inside a single unit of RDWC was found to be an attractive approach.…”
Section: Introductionmentioning
confidence: 99%
“…However, these energy and capital costs of the separation section can potentially be improved by utilizing DWCs for biobutanol recovery instead of conventional distillation columns, leading to a reduction in production costs of the process and thus have a significant impact in improving the competitiveness of biobutanol as a gasoline replacement. This application of DWC technology has not been previously investigated for biobutanol recovery from a thermochemical process, and is an interesting area of research as past research has demonstrated the benefits of DWC applications to bioethanol, bioDME and biodiesel production processes [16,17].…”
Section: Introductionmentioning
confidence: 99%